A Penchant for Protest?: Typifying Canadian Millennials' Political Engagement. Issue 2 (1st December 2021) - Hart, Randle J.
Abstract: Much has been made of the Millennial generation's seemingly low rates of political participation. Some argue that this generation is politically apathetic, while others suggest that Millennials have eschewed traditional politics in favor of protest as a means of political participation. Drawing on Canada's 2013 General Social Survey (Cycle 27, Social Identity), I employ an exploratory latent class analysis to determine whether the Millennial generation can be usefully categorized according to their participation in various forms of political, civic, and social movement activities. I then use binary logit regression to determine how well the biographical availability hypothesis explains Millennial politics. This research reveals that Canadian Millennials may be grouped into four categories: the politically unengaged, the politically expressive, the civically engaged, and activist . Support for the biographical availability hypothesis is mixed. As expected, students are more likely to be activists and parenthood reduces the odds of being politically expressive or an activist, but home ownership does not decrease the chances of Millennials being politically engaged and increases the chances of being civically engaged. Younger Millennials (ages 15–24) are much more likely to be politically unengaged compared to older Millennials (ages 25–34).